Railway engineering - Chandra, S.; Agarwal, M. M. (Oxford higher education., 2013)
This Second Edition provides an exhaustive coverage of all aspects of railways, at a level suitable for undergraduate students of civil engineering. With a balanced amalgamation of fundamental concepts and modern technological developments, this revised edition will prove equally beneficial for students of polytechnics as well as those preparing for the AMIE examination. Absorbing the latest developments on Indian Railways, the book presents various modernization plans covering tracks, locomotives, and rolling stock. To make the coverage comprehensive, it incorporates important statistical data and examples. Supplemented with a number of illustrations and examples, the text aids easy understanding of the design methods discussed.